Phan Duy Nhân - thơ và đời (Đà Nẵng Đà Nẵng, 2015)
Tổng hợp các bà thơ và bài viết của Phan Duy Nhân
Thư mục ở cuối sách
Keywords: Phan Duy Nhân -- 1941-; Thơ Việt Nam -- Phan Duy Nhân; Việt Nam; Phan Duy Nhân; Thơ Việt; Văn học Việt Nam; Thơ